Development of a Novel Clinical Classification for Radiation-induced Cystitis: The Portuguese Navy Radiation-induced Cystitis (PNRC) Scale - Tiago Ribeiro de Oliveira; Carla D’Espiney Amaro; Sérgio Henriques Pereira; Afonso Sousa Castro; Pedro Gomes Monteiro; João Cardoso Felício; Guilherme Bernardo; João Chambino; José Palma dos Reis; Chandra Shekhar Biyani (European Urology Open Science)
Background and objective: Radiation-induced cystitis (RIC) is an important consequence of pelvic radiotherapy that can cause high morbidity and, in extreme cases, mortality. The lack of a widely accepted classification system makes it difficult to compare treatment regimens. Our aim was to develop a new classification system covering the RIC spectrum to improve treatment comparisons and accurate incidence estimates for systematic use in clinical and research settings. Methods: A three-phase project was planned. Phase 1 involved a literature review and development of the Portuguese Navy Radiation-induced Cystitis (PNRC) scale. In phase 2 the scale was applied to 20 clinical cases. Phase 3 involved assessment of the applicability, relevance, inter-rater reliability, and usability of the scale using numerical and graphical methods to achieve consensus among international experts. Key findings and limitations: In phase 1, the panel analysed 13 existing classification systems and developed the PNRC scale, a comprehensive system encompassing five clinical domains: haematuria, other lower urinary tract symptoms, functional impairment, endoscopic findings, and therapeutic interventions. In phase 2, 114 experts from 30 countries completed the first validation round. Consensus was reached for 85% of cases. In phase 3, consensus was reached among 61 experts on the relevance and appropriateness of each domain, and on the exhaustiveness, hierarchy, clarity, mutual exclusivity, and clinical utility of the PNRC scale. Study limitations are the inclusion of only Medline-indexed manuscripts in the review and minor dispersion of responses, indicating subjectivity in the analysis of clinical case scenarios. Conclusions and clinical implications: The PNRC scale showed reliability and face and construct validity in the stratification of RIC severity for clinical cases. Patient summary: Radiation-induced cystitis is a debilitating complication of pelvic radiotherapy. A uniform classification system is needed to assess the incidence of this disease and to compare the results for different treatment options. We developed the Portuguese Navy Radiation-induced Cystitis (PNRC) scale, which was validated by an independent group of experts from 30 different countries.